Unplugged computing and computational thinking: approaching the subject as an Extension Curricular Unit - Liberalino, Carlos H. P.; B. Neto, Raimundo N.; S., Gisélia Cristina M. de; Pinto, Maria E. da S. (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento Digital, 2025)
Introduction: Software Engineering education requires the development of both technical and interpersonal skills, making it essential to adopt more practical and participatory approaches. In this context, ProjectBased Learning (PBL) has emerged as an effective strategy to foster greater engagement and the practical application of course content. Objective: This study aims to report the experience of applying PBL in the Software Engineering I course of a Computer Science undergraduate program at a public institution. Methodology: The research followed an action research approach, involving questionnaires, interviews, and participant observation. Students developed real-world projects, progressing through stages such as requirements elicitation, modeling, and prototyping. Results: The data revealed increased student engagement, development of technical and socio-emotional skills, and a positive evaluation of the methodology by participants.